The Use of Mediation as an Alternative Dispute Resolution in Village Dispute Resolution - Sabela Gayo (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
In the current conditions of the covid 19 pandemic and conciliation, it is possible to have disputes, especially those that occur in rural areas, the settlement of village dispute problems is stipulated based on Law No. 6 of 2014, so that the law expands the scope of the law in the settlement of disputes in rural communities and reduce the burden of cases in court. In law No. 6 year 2014 forward mediation as an alternative dispute resolution which is also one of the efforts to revive the culture and empower local wisdom in managing local wisdom. From the results of the study it is clear that alternative dispute resolution through mediation is very effective in maintaining good relations and kinship as the characteristics of the Indonesian nation